A holistic aesthetic experience model: Creating a harmonious dining environment to increase customers' perceived pleasure. (December 2020) - Horng, Jeou-Shyan; Hsu, Hsuan
Abstract: For chasing a harmonic condition among all elements and customers' positive emotion-pleasure in a restaurant, this study constructs a holistic aesthetic experience model within the context of a restaurant through the consensus opinions of experts who have aesthetics-related experience and work in the restaurant relevant organizations. This study adopted a mixed study, multiple-criteria decision-making (MCDM) approach for forming a solid and practical model. Four dimensions—physical environment, product and service, employee's aesthetic traits, and other customer's aesthetic traits —and twenty-three with an influential network relation map (INRM) for finding the roots of influence and influential weights for the further practitioners' decision making. The study contributes to the aesthetic theory and practical implementation in the hospitality industry.